Cenas de enunciação e ethos discursivo: análise do discurso de autoajuda para adolescentes - Furlan, Marília Molina [UNESP] (2013)
This research aims to analyze the discourse of self-help for teenagers, through theoretical and methodological apparatus of Discourse Analysis of French Line, with emphasis on reflections developed by Maingueneau about the notion of discursive ethos. We selected and describe four representative works of this discourse. The interest in the concept of discursive ethos, defined by Maingueneau (2005) as the image of the subject that states projects from himself by his enunciation, is justified by the role that image, linked to social stereotypes, plays in the process of adhesion of public to discourse, this is, the ethos is directly linked to the effectiveness discourse. In addition, ethos participates of the constitution of scenography of discourse, scene that discourse presupposes to be stated and that it validates by his own utterance. Considering aspects of linguistic materiality of the works of the corpus, the analysis reveals the heterogeneity both of ethe of self-help discourse for teenagers as the scenography articulated these ethe. The analysis also indicates that in the four surveyed works there are different ethe and scenography than those relating to self-help discourse for adults. Thus, in three of the analyzed works, we observe the attenuation of typical authoritative tone of this self-help discourse for adults. On the other hand, one of the works of the corpus, American work translated in Brazil, is closer to self-help discourse for adults, because it has the same authoritative tone that characterizes this type of self-help discourse